Господин из Сан-Франциско: рассказ / И. А. Бунин - Бунин Иван Алексеевич (Школьная библиотека, 1980)
Экземпляры: ф. 1 (20190417) / Инвентарный номер: 110032 / Цена: 3.00 / Авт.знак: Б 91 / ГРНТИ: 17.82 / ББК: Д